Labor Under Fire : A History of the AFL-CIO since 1979 - Minchin, Timothy J. (Book collections on Project MUSE., 2017)
From the Reagan years to the present, the labour movement has faced a profoundly hostile climate. As America's largest labour federation, the AFL-CIO was forced to reckon with severe political and economic headwinds. Yet the AFL-CIO survived, consistently fighting for programs that benefited millions of Americans, including social security, unemployment insurance, the minimum wage, and universal health care. With a membership of more than 13 million, it was also able to launch the largest labour march in American history, 1981's Solidarity Day, and to play an important role in politics. In a history that spans from 1979 to the present, Timothy J. Minchin tells a sweeping, national story of how the AFL-CIO sustained itself and remained a significant voice in spite of its powerful enemies and internal constraints.